FEATURES INTELLECTUALIZATION OF COMPUTER-INTEGRATED MANUFACTURING BASED ON THE MULTIDIMENSIONAL FUZZY CONTROLLER - Osinov, C. (Енергетика і автоматика, 2016)
In this article the theoretical  questions  of  instrumentation design for computers system and metodology of reengineering of business proceses  for   agriculture produsers  was considered.  The implementation of  the instruments with using the  biological feedback and self-organization proceses in computer system may to give the advantage in agriculture business. The feature of     control system with sensor for identification  the parametrs  of  biotechnical object was studyed.